The effect of intelligent business process management model on performance of smes mediated by innovation - Al Ali, Saeed Yousif Ahmed Ali (2023)
Small and Medium Enterprises (SMEs) in the UAE play a crucial role in driving the country's economic growth. However, their lack of innovation impedes their competitiveness in the business landscape. Although past research has explored methods to enhance SME performance, such as the use of artificial intelligence (AI) and business process automation, understanding the factors influencing the successful adoption of these technologies in the UAE's unique business environment remains a challenge. This study aims to fill these gaps by exploring the factors influencing the adoption of Intelligent Business Process Management (iBPM) among UAE SMEs. It examines the effect of iBPMadoption on SMEs' innovation and performance while evaluating the role of innovation as a mediating factor between iBPM adoption and performance. The study also proposes a comprehensive model capturing these relationships, framed by the Technology-Organization-Environment Framework. To achieve these objectives, a survey design was employed, and a questionnaire was distributed to SMEs via simple random sampling. The data collected from 377 respondents were analyzed using SPSS PLS-SEM Smart PLS software version 3.2.8. The findings of this study reveal that IT Infrastructure, Employees Competencies, Organizational Culture, and Strategic Alignment significantly influence iBPM adoption. However, factors such as Management Support, Government Support, and Market Condition do not have a significant impact, suggesting that organizational and environmental factors may not be strong drivers of iBPM adoption among SMEs in the UAE. Furthermore, iBPM adoption was found to have a positive influence on innovation and organizational performance. The positive relationship between iBPM adoption, innovation, and performance highlights the importance of adopting iBPM for enhancing competitiveness in the UAE. Importantly, innovation was found to partially mediate the relationship between iBPMand organizational performance, emphasizing the importance for SMEs to focus on nurturing innovation and integrating it into their iBPMinitiatives to achieve greater benefits. These findings contribute to the development of SMEs by providing insights into how iBPM adoption and innovation can enhance their performance and competitiveness, ultimately aligning with the UAE's strategic goals. Additionally, they guide SMEs and policymakers in devising strategies to promote iBPM adoption and foster a more innovative and competitive SME sector.